Pembelajaran Pendidikan Agama Islam Bagi Anak Penyandang Tunagrahita Ringan di SLB Mutiara Madani Kec. Matur - M Khalid Alwakkiyah; Yulia Rahman (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research aims to find out how PAI learning is done at SLB Mutiara Madani in general, apart from that, it is also to find out how PAI learning is for mildly mentally retarded students in depth and also to find out what challenges teachers face in learning PAI for mildly mentally retarded students and what are the PAI subjects for mildly mentally retarded students in the future. This type of research is qualitative research with data collection techniques through interviews, documentation and observation. For PAI learning in SLB, in general, the independent curriculum is used. In PAI learning, teachers use various media and methods. For PAI learning for mildly mentally retarded students, teachers also use various media and methods, such as poster media and lecture and bullying methods, for assessment the teacher uses summative assessment, formative assessment. In terms of infrastructure that supports PAI learning, at SLB there are already Iqro, Al-Quran and religious books that students can use. The challenge of PAI lessons for mildly mentally retarded students is the lack of parental attention towards their children so that their children only study at school, apart from that students are difficult to collaborate with and difficult to organize in learning. Students are also slow in responding and understanding what the teacher says so the teacher often repeats the same material. The opportunity is that SLB Mutiara Madani can accommodate more students with mild intellectual disabilities.